PENGARUH BRAND AMBASSADOR DAN BRAND AWARENESS TERHADAP MINAT BELI DI TOKOPEDIA (STUDI KASUS MAHASISWA UNIVERSITAS SURAPATI) - Chalifah, Nizmah; Susilo, Herman (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
The development of online commerce has become a phenomenon in the economy of a country that is expected to have a positive impact on the prosperity of digital economic equality in Indonesia. Especially when the Covid-19 pandemic occurred, the trend of online shopping became the main choice of consumers. Tokopedia is one of the online malls in Indonesia that carries the marketplace and online mall business model. The analysis model used is multiple linear regression analysis. Sample selection is done by accidental sampling. The sample amounted to 100 respondents, using multiple linear regression analysis. The results of the regression test showed that 49.5% of buying interest factors could be explained by brand ambassadors and brand awareness while the remaining 50.5% were explained by other factors not studied in this study. While the results of the F test show that simultaneously the variables of brand ambassador and brand awareness simultaneously have a positive and significant effect on buying interest. The results of the T test show that the brand ambassador variable shows that the results of the analysis do not have a positive and significant effect. then brand awareness partially has a positive and significant effect on buying interest in Tokopedia for Surapati University students.